Analisis Manajemen Komunikasi Pemerintah Kecamatan Laweyan Kota Surakarta untuk Mencapai Tujuan Organisasi - Kusharsanto, Adhika Prasetya (The Manager Review, 2025)
This study aims to analyze the communication management strategies of Laweyan District in improving organizational performance effectiveness in line with the vision and mission of the Surakarta City Government. Laweyan is known as a historic area, the birthplace of Syarekat Dagang Islam (SDI) and the center of the batik industry in Indonesia. The research method used qualitative descriptive analysis with a naturalistic approach without experimentation. The analysis focused on Michael Kaye's six communication management objectives and the PPM School of Management's six communication management functions. Primary data was obtained through interviews with the Head of Laweyan Subdistrict, the Head of Administration and Personnel, and subdistrict employees. Secondary data was obtained from the 2024 Laweyan Subdistrict Profile Book and the official website. The results of the study show that communication strategies have included coordination through WhatsApp Groups, regular roll calls, Zoom Meetings or Google Meets, and the use of social media. In addition, Laweyan Subdistrict formed a special conflict management team with the support of psychologists from the Surakarta City Government, which was an innovation in communication management. Communication management in 2025 proved to be effective and efficient, as evidenced by the minimal number of conflicts and an increase in performance indicators compared to 2024. These improvements include service orientation, accountability, competence, harmony, employee loyalty, adaptability, and collaboration. The Community Satisfaction Index also increased from 95.2 in 2024 to 96.1 in 2025. These results confirm that integrated communication can strengthen the performance of government organizations at the subdistrict level.